Driving Employee Performance in Agribusiness: The Role of Technology Adoption, Emotional Intelligence, and Digital Competence - Mahrani, Sri Wiyati; Nurdiani, Tanti Widia; Pramono, Susatyo Adhi; Aulia, Muhammad Reza; Apramilda, Riesna (Jambura Agribusiness Journal, 2024)
This research is intended to examine the impact of technology adoption in work processes, emotional intelligence, and digital competence on the performance of the employees in agribusiness companies. Adopting the quantitative strategy with the survey technique, data were obtained from the surveys with the responses of 180 agribusiness employees. Structural Equation Modeling (SEM) with the help of the SmartPLS 4 program has been used as the technique to conduct the analysis. The findings reveal the significant influence of technology adoption in work processes towards employee performance. It also indicates the significant influence of emotional intelligence, which validates the significance of the management of emotions in the face of modern work dynamics. Digital competence is found to be an essential prerequisite in maximizing the efficiency and productivity in work, especially in the application of agricultural information systems and IoT-based technologies. This research offers managerial implications in the form of recommendations to management in the agribusiness to put more emphasis on technology training as well as the soft skill development of employees. The research also enriches the knowledge with the integration of technological as well as psychological orientations existing in the context of agribusiness, which has remained relatively under-theorized empirically.